Respuesta :
Answer:
The correct answer is D. -5 +/- i√2
Step-by-step explanation:
Let's solve for x, the equation given to us, this way, using the quadratic formula:
x = (- b +/- √b² - 4ac)/2a
Replacing with the real values, we have:
x = (-10 +/- √10² - 4 * 1 * 27)/2
x = (-10 +/- √100 -108)/2
x = (-10 +/- √-8)/2
x = (-10 +/- √-1 * 4 * 2)/2 Let's recall that √-1 = i
x = (-10 +/- 2i√2)/2
x = 2 (-5 +/- i√2)/2 (Dividing by 2 both the numerator and the denominator)
x₁ = -5 + i√2
x₂ = -5 - i√2
The correct answer is D. -5 +/- i√2
Answer:
The solution is [tex]-5(+-)1.4i[/tex]
Step-by-step explanation:
- To calculate the roots of a quadratic equation , you should remember the well known formula : [tex]\frac{-b(+-)\sqrt{b^2-4ac} }{2a}[/tex], where "a" is the term linked to the squared term, "b" is the term linked to the linear term, and "c" is the constant term.
- In this case, a=1, b=10 and c=27. Then, applying this formula means doing the following calulations: [tex]\frac{-10(+-)\sqrt{10^2-4\times1\times27} }{2\times1} =\frac{-10(+-)\sqrt{100-108} }{2} =\frac{-10(+-)\sqrt{-8} }{2}[/tex].
- Because we know that the imaginary unit is [tex]i=\sqrt{-1}[/tex], or alternatively, [tex]i^2=-1[/tex], we can express the previous expression as follows: [tex]\frac{-10(+-)\sqrt{8\times(-1)} }{2}[/tex].
- We can now apply distributive property of the radical of a product , and obtain the following:[tex]\frac{-10(+-)\sqrt{8}\times\sqrt{-1}}{2} =\frac{-10(+-) 2.83i}{2} =-5(+-)1.41i[/tex], which is our final expression.